WAYS TO INCREASE THE EFFECTIVENESS OF THE MONETARY SYSTEM UNDER THE CONDITIONS OF SUSTAINABLE DEVELOPMENT OF THE NATIONAL ECONOMY - A. Amanov,; E. Buribaev,; A. Abduvohidov,; I. Abdugapporov, (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the role and tasks of monetary policy in improving the effectiveness of ongoing large-scale reforms in the country at the present stage of economic development.